Long‐term effectiveness of biodegradable patent foramen ovale closure: Are we there yet?. Issue 3 (17th February 2020) - Parikh, Puja B.; Reilly, John P.
Key Points: Given increasing performance of left‐sided structural heart interventions, transseptal puncture following prior patent foramen ovale (PFO) closure can be challenging. The biodegradable BioSTAR, an attractive alternative to permanent PFO closure devices, demonstrated comparable long‐term closure rates compared to the Amplatzer PFO device. Long‐term peri‐device left‐to‐right shunt and nitinol strut protrusion with the BioSTAR must be taken into account in design of future PFO devices with biodegradable capabilities.